2021
DOI: 10.2196/25484
|View full text |Cite
|
Sign up to set email alerts
|

Distance Management of Spinal Disorders During the COVID-19 Pandemic and Beyond: Evidence-Based Patient and Clinician Guides From the Global Spine Care Initiative

Abstract: Background The COVID-19 pandemic has greatly limited patients' access to care for spine-related symptoms and disorders. However, physical distancing between clinicians and patients with spine-related symptoms is not solely limited to restrictions imposed by pandemic-related lockdowns. In most low- and middle-income countries, as well as many underserved marginalized communities in high-income countries, there is little to no access to clinicians trained in evidence-based care for people experiencin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Eighteen articles/guidelines (59% of all the articles/guidelines), including most of the UK AHP professional bodies’ guidelines (n=7), stated the purpose of the guidance. They indicated that telehealth can be used for a variety of services including triage, 20–23 advice provision, 21 22 24 assessment, 18 19 22 25 intervention, 25–27 provision of piece of equipment, 18 remote monitoring, 23 24 26 27 service evaluation, 22 patient education, 21 24 27 consultations with other AHPs 22 26 and staff supervision. 24 27 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen articles/guidelines (59% of all the articles/guidelines), including most of the UK AHP professional bodies’ guidelines (n=7), stated the purpose of the guidance. They indicated that telehealth can be used for a variety of services including triage, 20–23 advice provision, 21 22 24 assessment, 18 19 22 25 intervention, 25–27 provision of piece of equipment, 18 remote monitoring, 23 24 26 27 service evaluation, 22 patient education, 21 24 27 consultations with other AHPs 22 26 and staff supervision. 24 27 …”
Section: Resultsmentioning
confidence: 99%
“…Eight articles/guidelines 19 21 25 26 29 32 38 mentioned that AHPs should make patients aware of the risks and limitations associated with telehealth. Risks related to a potential breach of privacy, confidentiality and security were acknowledged in five articles/guidelines, 19 25 26 29 32 limitations related to the assessments and treatments provided remotely in four 21 25 26 32 and other non-specified risks in two. 25 38 It was stated that patients should also be informed about the differences between telehealth and face-to-face consultations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID-19 pandemic has led to demanding challenges in treating and diagnosing patients with spinal disorders such as lumbar disc herniation [ 22 , 23 , 25 ]. Meanwhile various guidelines for distance management of, e.g., spinal disorders have been published; however, the field of telemedicine still requires further research, validation and consequently improvement in order to provide the patients sufficiently [ 22 , 25 , 42 ]. As reported by Minghelli et al, the majority of physiotherapists interrupted their work in person and the overall accessibility and availability of physiotherapy has decreased during the ongoing pandemic [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…23 A recent international, interprofessional expert team developed patient and clinical guides to help triage cases and inform the use of telehealth in management of spinal disorders. 39 This represents an opportunity for chiropractors to facilitate continuity of care through the use of telephone and/or video methods. 21,40 In our study of chiropractic use of telehealth in the VHA, with the increased use of telehealth services, telephone visits were more frequently seen than video visits.…”
Section: Discussionmentioning
confidence: 99%